Polymer nanocomposites: Synthetic and natural fillers a review - Gacitúa E., William; Ballerini A., Aldo; Zhang, Jinwen (Maderas. Ciencia y Tecnología, 2025)
This paper reviews current research, techniques for characterization and trends on the field of nanocomposites. Nanocomposites are new materials made with fillers which have nanosize. These materials have a big potential for applications in the automotive and aerospace industry as well as in construction, electrical applications and food packing. There is a tremendous interest for using bionanoparticles like cellulose microfibrils or whiskers to be applied in the new era of biocomposites.